(untitled) (Biological Sciences - PJSIR, 2004)
Field experiments on sulphur fertilization in cotton cultivar CIM-109 were carried out at Central Cotton Research Institute Multan, Pakistan, in silty loam soils. The treatments consisted of four sulphur doses (0, 7, 14, 28 kg ha-1) and two sulphur sources (gypsum and ammonium sulphate). Sulphur fertilization showed significant increase in seed cotton yield, boll number and boll weight. The addition of 7 kg S ha-1 seemed sufficient to overcome deficiency in silty loam soils for optimum cotton production. There were no differences in seed cotton yield due to sulphur sources. The petiole sulphatesulphur concentration increased with increasing doses of sulphur fertilizer. The concentration of SO4?S > 2000 ppm seemed sufficient for normal cotton growth and optimum seed cotton yield.